Influence Culture Organization, Environment Work as well as Occupational Safety and Health (K3) on Employee Performance Through Motivation Work at PT Sidomulyo Selaras Tbk - Caraka Wedhatama, Rahadian; Riyanto, Setyo (DINASTI RESEARCH, 2025)
Study This aim For know Influence Culture organization, environment work, Health and Safety Occupational Health and Safety (K3) on Employee Performance Mediated by Motivation Work at PT Sidomulyo Selaras Tbk. Research methods This use quantitative. Population in study This as many as 150 employees fixed. Sampling techniques in study this using simple random sampling, with amount sample as many as 109 employees. Research data collected through distribution questionnaire. The data analysis method used was the Structural Equation Model – Partial Least Square (SEM-PLS). The research results show that: 1) Culture organization influential positive to performance employees, 2) Environment Work influential positive to performance employees, 3) Health and Safety Work (K3) has an impact positive to performance employees 4) Culture organization influential positive to performance employees mediated by motivation? work 5) Environment Work influential positive and significant to performance employees mediated by motivation? 6 ) Health and Safety Work (K3) has an impact positive and significant to performance employees mediated by motivation? work. Contribution study This is findings that can be used as base from policy management source Power man in increase performance company.